Comparison between Clinical and Bacteriological Profile of Febrile Neutropenic and Non Neutropenic Pediatric Leukemic Patients - Karim, A K M Rezaul; Maayenu,; Urmi, Rehnuma (Journal of Chittagong Medical College Teachers' Association, 2021)
Background: Infection is an important cause of morbidity and mortality in children with leukemia. To improve the quality of care and survival, it is important to understand the clinical presentation and bacteriological profile during febrile episodes of these patients. The aim of this study was to compare the clinical presentation and bacteriological profile of febrile neutropenic and nonneutropenic pediatric leukemic patients. Materials and methods: This was a cross sectional observational study conducted at Chittagong Medical College Hospital (CMCH) over a period of 12 months. Study population (n=60) were all hospitalized pediatric leukemic patients who were febrile and on anticancer chemotherapy. By purposive sampling two groups were made. Group A (n=30) was febrile neutropenic and group B (n=30) was febrile non-neutropenic patients. The Clinical presentation, bacteriological profile and antibiotics susceptibility patterns in both groups were analyzed. Results: Mean (±SD) age of the patients was 6.41±3.05 years. Acute Myeloid Leukemia (AML) patients were high in Group-A (60%) and Acute Lymphoblastic Leukemia (ALL) patients were high in Group-B(80%). Gastroenteritis, skin infection and sepsis were more in group A than group B (p<0.05). Upper respiratory tract infections were significantly more in group B than group A (p<0.05). Among 60 samples, 7 (12%) were blood culture positive for bacteria. The isolated organisms were E. coli, Klebsiellaspp, Salmonella, Staph aureus and others. Amikacin Meropenem and Vancomycin were the effective agents. Conclusion: Febrile neutropenic episodes were more common in AML patients undergoing chemotherapy. Gram negative sepsis, gastroenteritis and skin infection were high in febrile neutropenia, but upper respiratory tract infections were high in febrile non neutropenia. JCMCTA 2021 ; 32 (2) : 25-29